Literature Review: Extraction Methods and Antioxidant Activity of Rhizophora mucronata Leaves - Attaya, Kalisa; Saputri, Legis Ocktaviana; Permatasari, Lina (Jurnal Biologi Tropis, 2025)
Free radicals are highly reactive molecules and can trigger various degenerative diseases, so prevention efforts are needed through effective antioxidants. This study aims to review and analyze the extraction method of R. mucronata leaves in increasing antioxidant activity against DPPH free radicals. This study was conducted through a literature review of experimental research articles obtained from Google Scholar and PubMed databases using specific keywords, covering national and international publications for the period 2015-2025. The obtained articles were analyzed based on the extraction technique, solvent type, and IC₅₀ value reported in the article. The analysis showed that cold extraction methods, especially multi-step maceration with methanol solvent, can produce R. mucronata leaf extracts with very strong antioxidant activity with an IC₅₀ value of 0.04 ppm. The conclusion of this study confirms that extraction technique and solvent selection can affect the antioxidant activity of R. mucronata leaves. These findings support the need for optimization of extraction methods to maximize antioxidant effectiveness in the development of natural antioxidants.